Modelo acústico análogo ao buraco negro de Schwarzschild - Toniato, Júnior Diniz (2010)
There isn t experimental evidences that can validate the results of black holes termodynamics. This because the radiation emitted by the black hole, predicted by theory, it is almost impossible to be detected due to its low value of magnitude. In the search for clues that could validate the existence of this radiation, the study of analog models to those objetcs has grown considerably in recent decades. They allow the idealization of experiments in labs that would be extremely complicate to be done directly with the gravitational systems. A fluid in moviment can act on the sound the same way that curved space-time can influence on light trajectory in the general relativity. So, one can describe the propagation these sound waves through an effective metric, under wich they will follow null geodesics. This thesis makes a review of these studies focusing in an analogy to Schwarzschild black hole using an acoustic system, showing its advantages and limitations when applied in the study of Hawking s theory